Hidden Inequalities in the Workplace : a Guide to the Current Challenges, Issues and Business Solutions. - Caven, Valerie (Palgrave explorations in workplace stigma., 2017)
The book presents a critical framework for assessing whether organisational practice and function reinforces unseen potential differences amongst individuals in the workplace. It offers a comprehensive understanding and awareness of managerial and organisational practices that perpetuate social exclusion and discrimination towards individuals in the workplace. The book draws together themes of non-declared medical or physical conditions, voluntary and involuntary disclosure of difference, dietary requirements, lifestyle, organisational engagement and cognitive bias. As a result, the book provides a unique blend of scholarly and professional research, and brings those who have been affected by social stigmas and discrimination in the workplace to the fore. Hidden Inequalities in the Workplace also offers practical and strategic insights for practitioners, students and policy-makers, and delves the strategic nature of policy intervention and thought-provoking dialogue.